« Erika hätte so gern ein Bild von Koch ». Materielle Erinnerungskulturen in Mädchenschulen in Österreich und Deutschland in der ersten Hälfte des 20. Jahrhunderts - Li Gerhalter (Genre & Histoire)
« Erika would so much love a picture of Koch ». Material Cultures of Remembrance in Austrian and German Girls’ Schools in the First Half of the 20th CenturyThis text links questions of gender history and research on auto/biography and ego documents with the history of friendship and patronage, the history of emotions and a cultural studies’ approach to material culture. Taking diary entries and correspondences as its sources, the article identifies the objects (letters, friendship books and portrait photographs) that were passed on as mementoes among students and between students and teachers in Austrian and German girls’ schools during the first half of the 20th century. These material exchanges followed different logics whose constraints and potential changed over time. Girls’ schools are understood as social structures with a strictly hierarchical order, where formal relationships between students and teachers and informal relationships among classmates were closely intertwined. Although the same objects acquired value as memento between friends and teachers, their transfer mirrored the school hierarchy. In brief, the following patterns are observed: the girls tried to obtain letters, friendship book entries and photographs from their peers as well as from their teachers; the latter, however, rarely granted these requests. Teachers did not collect mementoes of their students. Almost exclusively teachers determined the transfer of memento objects; thus, this form of a material remembrance culture contributed to re/produce the school’s internal power structures.At the same time, these hierarchies could be challenged, particularly through the technical innovations of private amateur photography from the 1920s on. This development changed the respective positions of students (who owned a camera) and of teachers (whose photographs were taken, at times without their knowing).Finally, this text considers the detailed descriptions of gift transfers in the girls’ ego documents and analyses their significance within this system. In particular, such descriptions gave girls an opportunity to preserve memories, determining the content at their own discretion, without incurring any financial cost.Generally, the author interprets this material culture of remembrance (students’ desire to own objects as mementoes of colleagues and of teachers and students’ descriptions of the objects and their transfer in diaries and letters) as an expression of their identification with the school as an institution, which could also strengthen the girls’ sense of community with each other.